THE INFLUENCE OF RETAIL STORE CHARACTERISTICS ON CONSUMER PURCHASE INTENTION (CASE STUDY IN MULTI MART MEGA MALL MANADO) - Manan, Friska Mentari (Sam Ratulangi University, 2015)
ABSTRACT To fulfill customersâ€™ needs and wants, companies create and offer products and services to consumer. In order to offer products and services, a company needs a distributor to sell their products or services directly to consumer. Ajzen theory is used in this research of consumer purchase intention. The purpose of this study is to analyze which retail store characteristics; product assortment, service quality, store atmosphere, and store location influence on purchase intention. This study is using purposive sampling technique by distribute 100 questionnaires to the people who have visited Multi Mart Mega Mall Manado and using Multiple Regression Analysis. As a result, retail store characteristics influence on consumer purchase intention simultaneously. Service quality and store location are significantly influence on consumer purchase intention partially, whereas product assortment and store atmosphere does not influence on consumer purchase intention. Multi Mart Mega Mall should provide a good service and comfortable atmosphere to attract more consumers. Keywords: Product Assortment, Service Quality, Store Atmosphere, Store Location, Purchase Intention. Â